The Implementation of the Integrated STEAM Approach to Improve Students' Interest in Science - Almuharomah, Farida Amrul; Sunarno, Widha; Masykuri, Mohammad (International Journal of STEM Education for Sustainability, 2023)
The study aimed to analyze indigenous scientific knowledge into scientific knowledge through the STEAM approach. Interesting online learning can be done by integrating the local culture of the Plancungan Village. This research uses the Quantitative Descriptive method. Based on research at seven schools in Ponorogo found 83,3% of teachers never used the local culture because teachers know no understands the local culture of the Plancungan village in science material. Respondents were 62 students from Junior High School 1, Junior High School 2, and Junior High School 3. 37,74% of students know this local culture. The value of local culture is contained in the process of making pottery, namely character, aesthetic, historical, and environmental values. STEAM analysis, including science on the process of making pottery, requires a tool in the form of a turntable called "Perabot". This turntable is a form of Simple Plane. Simple Planes are tools that can facilitate human work. The math is in the Mechanical Advantage of the "Perabot" which can be calculated by dividing the wheel's radius by the axle's radius. Engineering on the body has the greatest ratio of volume to overall proportion. The moth is smaller than the neck, which is adapted to its function. Traditional pottery-burning technology uses a field stove with husk, straw, and bamboo as fuel. The art of pottery can be seen in form, color, and function. STEAM analysis on the pottery-making process can increase students' interest in science. The student's interest in learning science obtained an average N-gain of 0.70 with high criteria. The resulting STEAM analysis can also be applied to e-modules, e-learning, e-books, etc.